The failure at god school. 1 - Hyūga, Natsu (Yen Press, 2025)
"Nagi's normal! Gods are supposed to give girls like her divine aid, not invitations to the most prestigious magic academy in Japan!! Modern life means modern solutions, even to supernatural problems. So of course the government would have a classification system, special schools, and licenses for people with mysterious powers. but only those with full certification may use the title of God. And high schooler Nagi is in serious need of a god! The death of her grandmother has left her family shrine devoid of the necessary divinity. But if Nagi isn't careful, her search for a god might end with her finding more than she bargained for..." -- publisher.